Kiss-Up-Kick-Down to Get Ahead: A Resource Perspective on How, When, Why, and With Whom Middle Managers Use Ingratiatory and Exploitative Behaviours to Advance Their Careers - Fabiola H. Gerpott; Niels Van Quaquebeke (Journal of Management Studies, 2022)
There are myriad organizational anecdotes about middle managers who advance their careers by ingratiating themselves with their superiors while exploiting and abusing their subordinates. We formally define this behavioural combination as the Kiss-Up-Kick-Down (KUKD) phenomenon and develop a resource-focused framework that not only explains when middle managers will engage in KUKD, but also how such behaviour helps their career progression via three resource-related pathways: One path involving sponsorship resource gains from superiors, another path involving productive resource gains from subordinates, and an intra-individual path related to middle managers' own psychological resources. Staying within the resource framework, we theorize that superiors and subordinates become likely targets of KUKD when the former is resource-poor and the latter is resource-rich. Finally, we deliberate on the role of time as a crucial boundary condition: not only in terms of when middle managers engage in KUKD behaviours, but also how such actions involve diminishing returns.
Keywords: 650; conservation of resources; exploitative leadership; ingratiation; Kiss-Up-Kick-Down; middle managers; time